Analysis of epidemiological factors for pelvic floor defects in Indian women - Parulekar, Maitreyee S.; Parulekar, Shashank V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pelvic floor defects is one of the commonest conditions requiring gynecological reference. This study was aimed at evaluation of epidemiology which would help us in having a better understanding regarding the prevalence, risk factors, the natural course and associated complications of the disease in Indian women where the number of women presenting with pelvic floor defects is on a rise but there is a considerable lack of research in literature as compared to the western population. Methods: It was an observational, non-interventional, prospective type of study including 88 patients over a period of 3 years at the department of obstetrics and gynecology at a tertiary hospital in Mumbai, Maharashtra, India. Results: The mean age of the patients was 52.38±11.35 years, 54 (61.36%) of the patients were of postmenopausal age group. The mean duration for which the complaints were present were 48±6.73 months. Seventy-six patients (86.83%) presented with complaints of mass per vagina, 22 patients (25%) had history of prolonged labor and 9 patients (10.2%) had history of instrumental delivery. Eighty-six women (97.72%) had history of all vaginal deliveries and only 4 (4.54%) patients had history of a caesarean section. Forty-four patients (55.69%) of patients had grade 3 utero-vaginal descent, 74 patients (84.09%) presented with cystocele and 79 (89.77%) of the patients presented with rectocele. Conclusions: This paper provides an insight into the factors affecting the prevalence of this disease in Indian women and the unique differences from other populations.